Cytokeratin-14 contributes to collective invasion of salivary adenoid cystic carcinoma. - Xiao-Lei Gao; Jia-Shun Wu; Min-Xin Cao; Shi-Yu Gao; Xiao Cen; Ya-Ping Jiang; Sha-Sha Wang; Ya-Jie Tang; Qian-Ming Chen; Xin-Hua Liang; Yaling Tang (PLoS ONE)
Collective invasion of cells plays a fundamental role in tissue growth, wound healing, immune response and cancer metastasis. This paper aimed to investigate cytokeratin-14 (CK14) expression and analyze its association with collective invasion in the invasive front of salivary adenoid cystic carcinoma (SACC) to uncover the role of collective invasion in SACC. Here, in the clinical data of 121 patients with SACC, the positive expression of CK14 was observed in 35/121(28.93%) of the invasive front of SACC. CK14 expression in the invasive front, local regional recurrence and distant metastasis were independent and significant prognostic factors in SACC patients. Then, we found that in an ex vivo 3D culture assay, CK14 siRNA receded the collective invasion, and in 2D monolayer culture, CK14 overexpression induced a collective SACC cell migration. These data indicated that the presence of characterized CK14+ cells in the invasive front of SACC promoted collective cell invasion of SACC and may be a biomarker of SACC with a worse prognosis.